Case Report: Pulmonary sclerosing pneumocytoma mimicking as a neuroendocrine tumor on 18F-FDG and 68Ga-DOTATATE PET/CT: a case presentation - Yu, Ronghua; Zhao, Wei; Yu, Yonglin; Hu, Xianwen (Frontiers in Oncology, 2025)
Pulmonary sclerosing pneumocytoma (PSP) is a relatively rare benign lung tumor, and it is difficult to obtain an accurate diagnosis before surgery. Herein, we present a case of 34-year-old woman who came to our hospital for medical help due to cough and sputum for one month. She underwent a chest computed tomography (CT) scan which revealed a circular soft tissue density shadow in the upper lobe of the left lung. A needle biopsy was subsequently performed which revealed a probable lung carcinoid. To further evaluate the nature of the mass and determine a treatment plan, the patient subsequently underwent dual nuclide tracer including fluorine-18 labeled fluorodeoxyglucose (18F-FDG) and gallium-68 labeled 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7,10-tetraaceticacid -D-Phel-Tyr3-Thr8-OC (68Ga-DOTATATE) PET/CT imaging. The results showed that the lession presented increased both 18F-FDG and 68Ga-DOTATATE uptake, suggesting a neuroendocrine tumor. However, postoperative pathology confirmed that the lesion was PSP. Our case study suggests that PSP may presents varying degrees of increased 18F-FDG and 68Ga-DOTATATE uptake on positron emission tomography (PET)/CT imaging, which should be considered as one of the differential diagnoses for lung carcinoids.